Rapid expression of RASD1 is regulated by estrogen receptor-dependent intracellular signaling pathway in the mouse uterus. (5th May 2017) - Kim, Hye-Ryun; Cho, Kil-Sang; Kim, Eunhye; Lee, Ok-Hee; Yoon, Hyemin; Lee, Sangho; Moon, Sohyeon; Park, Miseon; Hong, Kwonho; Na, Younghwa; Shin, Ji-Eun; Kwon, Hwang; et al.
Abstract: Dexamethasone-induced RAS-related protein 1 (RASD1) is a signaling protein that is involved in various cellular processes. In a previous study, we found that RASD1 expression was down-regulated in the uterine endometrium of repeated implantation failure patients. The study aim was to determine whether RASD1 is expressed in the endometrium of mouse uterus and how it is regulated by steroid hormones during the estrous cycle. In this study, we investigated RASD1 expression and regulation in an ovariectomized female mouse model. Rasd1 mRNA was highly expressed in mouse reproductive tissues, including the uterus. Rasd1 expression was detected exclusively in the endometrial epithelium at the proestrus stage of the estrous cycle. Rasd1 expression in uteri increased with administration of estradiol, but not progesterone. Its expression was rapidly induced within 2 h after E2 treatment. Pretreatment with ICI 182, 780, an estrogen receptor antagonist, reduced RASD1 protein expression. In addition, we identified that rapid expression of Rasd1 was mediated by the estrogen intracellular signaling including both p38-mitogen-activated protein kinase and the extracellular signal-regulated kinase. These findings suggest that RASD1 acts as a novel signaling molecule and plays an important role in regulating dynamic uterine remodeling during the estrous cycle in the uterus. Highlights: RASD1 is exclusively localized in luminal and glandular epithelium of the uterus. RASD1 expression is dynamically regulated in the uterus during the estrous cycle. Estrogen treatment rapidly increased the expression of RASD1 in ovariectomized mice and prepubertal mice. The rapid induction of RASD1 is mediated by intracellular signaling p38-MAPK and ERK1/2 factors.